1998
DOI: 10.1200/jco.1998.16.1.301
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravenous continuous infusion of fluorouracil compared with bolus administration in advanced colorectal cancer. Meta-analysis Group In Cancer.

Abstract: 5-FU CI is superior to 5-FU bolus in terms of tumor response and achieves a slight increase of overall survival. The hematologic toxicity is much less important in patients who receive 5-FU CI, but hand-foot syndrome is frequent in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

1998
1998
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 855 publications
(81 citation statements)
references
References 14 publications
2
78
0
1
Order By: Relevance
“…Besides higher response rates, this combination also showed an improved survival in a meta-analysis [24]. Recently, a meta-analysis showed a significantly higher response rate when 5FU was administered as a continuous infusion in patients with colorectal cancer compared to 5FU bolus injection (23 vs. 14%, respectively) [25]. …”
Section: Ts As a Target For Treatmentmentioning
confidence: 99%
“…Besides higher response rates, this combination also showed an improved survival in a meta-analysis [24]. Recently, a meta-analysis showed a significantly higher response rate when 5FU was administered as a continuous infusion in patients with colorectal cancer compared to 5FU bolus injection (23 vs. 14%, respectively) [25]. …”
Section: Ts As a Target For Treatmentmentioning
confidence: 99%
“…The earlier mentioned study of Lorenz and Müller [30]supports this approach. Furthermore, in systemic treatment, chemical biomodulation of 5-FU by leucovorin resulted in significantly higher response rates [18]. Hepatic arterial leucovorin administration showed only a slight regional advantage, induced catheter thrombosis, and increased the risk of biliary sclerosis when combined with FUDR [40, 41]; consequently, intravenous leucovorin is the preferred route of administration.…”
Section: Results and Complications Of Hacmentioning
confidence: 99%
“…Furthermore, FUDR and 5-FU are cell-cycle-dependent drugs and a larger number of tumor cells in the S phase will be exposed to the drug by prolonged exposure. For systemic treatment, a meta-analysis of randomized trials found continuous infusion to be superior to bolus 5-FU in terms of response and survival [18]. In HAC, continuous infusion of FUDR and 5-FU is being used in most studies.…”
Section: Theoretical and Practical Aspectsmentioning
confidence: 99%
“…Early clinical trials confirmed the importance of constant exposure to 5-FU to obtain a therapeutic effect [3]. Protracted infusions appear to improve response and survival compared with bolus administration [4, 5]and the administration of 5-FU over prolonged periods of time may also be associated with reduced toxicity [4, 6]. The toxicity profile of 5-FU is schedule dependent.…”
Section: Introductionmentioning
confidence: 99%